Pulmonary and intestinal tuberculosis in a kidney transplant recipient - R. O. Kantariya; A. V. Vatazin; A. B. Zul’karnayev; V. A. Stepanov (Трансплантология (Москва), 2019)
Introduction. Tuberculosis is one of the most common infections in the general population, as well as among the recipients of solid organs. In kidney transplant recipients, the diagnosis of tuberculosis is often extremely difficult to make because of unclear clinical and radiological symptoms, and a highly frequent atypical (extrapulmonary) localization. The tuberculosis treatment in patients on drug immunosuppression is a significant problem.Clinical case. At five years after renal transplantation, the patient noted the onset of fever up to 38 degrees C. It was suspicious of respiratory infection. Chest X-ray, computed tomography, and ultrasound examination of the graft revealed no pathology. Antibacterial and antiviral therapy brought stable improvement. A repeated computer tomography demonstrated an enhanced pulmonary pattern in S6 of the left lung with visualization of small grouped lesions located peribronchially, the terminal ileitis in the abdominal cavity: (an intensive contrast accumulation in the mucosa of the affected part of the small intestine, the mesentery hypervascularity at this level). A colonoenteroscopy with a ileum intestine biopsy was performed; the findings were highly consistent with a tuberculous process. A targeted treatment of tuberculosis was carried out, which had a marked positive trend.Conclusion. Thus, the diagnosis of tuberculosis in kidney transplant recipients is complex; the clinical signs and instrumental test results are often ambiguous, which greatly complicates the timely diagnosis. An integrated approach with the use of modern diagnostic methods is required.